Pengaruh Customization dan Interdependensi terhadap Karakteristik Informasi Sistem Akuntansi manajemen Broad Scope dan Aggregation - Fivi Anggraini (The Indonesian Journal of Accounting Research, 2013)
This study examined  empirically whether the relation between customization and charateristic of management accounting systems specially broad scope and aggregation information is a direct one or whether the relation operates via interdependence. The purpose of this study is to reexamined the result of Bouwens (1998), Bouwens and Abernethy, (2000) study reveal there is no strong support for characteristic of broad scope management accounting systems and aggregation information for uncertainty in managerial decision making. This is different from earlier studies of Mia & Chenhall (1994), Abernethy & Guthrie (1994), Chong (1998). A theoretical framework is developed to study the effect of customization on the use charateristic of management accounting systems. This theory suggests that customization has a direct effect on the use charateristic of management accounting systems, but also that customization augments interdependence between departements which in turn effects charateristic of management accounting systems use. It is argued that the information required for decision making by managers in firms pursuing customization differs significantly from the requirements of managers in firms which produce primarily standardized products. Information requirements change not only in direct response to the pursuit of customization but also due to the increasing  interdependence which occur between functional departements.Path analysis is used to test the model. This study reveals that customization not increases interdependence in functionally differentiated structures. Partial support is found for a direct relationship between customization and characteristic of management accounting systems broad scope use. The result of this study can confirmation study Bouwens (1998), Bouwens dan Abernethy (2000) but there is no support to aggregation information. The other support is also found for a direct relationship between interdependence and management accounting systems aggregation information  and  there is no support for broad scope information. Data analysis revelas support for relation direct customization in charateristic of management accounting systems of broad scope information but it is not to aggregation information. Indirect customization not influences characteristic manage ment accounting systems broad scope and aggregation information use via interdependence. The study of 126 production dan sales managers further revealed difference in management accounting systems use of customization and interdepedence.